2020
DOI: 10.12911/22998993/123250
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Municipal Solid Waste Typology on Leachate Flow under Semi-Arid Climate – A Case Study

Abstract: As recently created, the landfill site of Oujda, Morocco receives an annual flow of municipal solid wastes of 140000 tons. It became clear that the leachate storage ponds were undersized compared to the actually emanating flows. With no adequate treatment, the storage time of leachates in deep and anaerobic ponds increase and produce olfactory nuisances directly affecting the air quality of the nearest agglomerations. The monitoring of leachate flows during a year, showed the daily average production of 126 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…The last parameter is significant since waste in Morocco has very high moisture, between 60% and 75% (Soudi & Chrifi, 2007). A study carried out in the landfill of Oujda city showed that the moisture of the waste received reached an average rate of 63.5% (Arabi et al., 2020). At the same time, Chiguer et al.…”
Section: Introductionmentioning
confidence: 99%
“…The last parameter is significant since waste in Morocco has very high moisture, between 60% and 75% (Soudi & Chrifi, 2007). A study carried out in the landfill of Oujda city showed that the moisture of the waste received reached an average rate of 63.5% (Arabi et al., 2020). At the same time, Chiguer et al.…”
Section: Introductionmentioning
confidence: 99%
“…Urban expansion and the development of Morocco's socioeconomic activities induce a gradual increase in solid waste (Bakraouy et al, 2017). The amount of waste has been estimated at 6.9 million tons/year, equivalent to 0.76 kg/inhab/day in urban areas and 0.3 kg/inhab/day in rural areas (Arabi et al, 2020;Hasib et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In which the proportion of putrescible fraction mainly dominated by Food Waste is on average 74% and reaches 77% during the summer season. Unfortunately, this waste is landfilled instead of being recycled, aggravating the negative impact of its treatment within the landfill cells due to its high humidity of 64% [7].…”
Section: Introductionmentioning
confidence: 99%